SERVICE IMPLEMENTATION OF CONSUMER INTEREST IN TEBING TINGGI BUSINESS CLINIC SUMATERA UTARA - Putra, M. Umar Maya; Damanik, Syafrida (International Journal of Research -GRANTHAALAYAH, 2020)
This research begins with the development of MSMEs (Micro, Small and Medium Enterprises) which is an illustration of strengthening regional potential. Developing MSMEs can improve services to consumers in order to create buying interest. The benchmarks that are assessed through the level of confidence in a product directly aim to analyze customer interest. In this study, it is explained that customer interest is product quality, service quality, price, and cost which are closely related to meeting the service needs of the Tebing Tinggi Business Clinic (KLIBI) assisted them. The method used is the canonical analysis method which is a multivariate model that studies the relationship between the dependent variable set varied from the independent variable set. The data characteristics for canonical correlation are metric data, namely interval or ratio data. The research result gained that responsiveness and concern give the significant effect on the cost so that customers want to buy continuously. For the recommendation, The Government needs to improve the quality of product endorsement among Tebing Tinggi and Indonesian consumers by making the program business promotion and international exhibitions through KLIBI.